THE BEGINNING OF THE HISTORY OF AMERICAN LEXICOGRAPHY (Konferensiyalar | Conferences, 2024)
The first American dictionary of the English language was compiled by a man whose name also Samuel Johnson Jr., a Connecticut Schoolmaster, was published in 1798 a small book entitled “A School Dictionary”.